Social entrepreneurial intention among working adults: An emerging country context - Yang, Qing; Al Mamun, Abdullah; Jingzu, Gao; Siyu, Long; Masud, Muhammad Mehedi (Frontiers in Psychology, 2023)
Under the premise of the value-belief-norm (VBN) model, this study examined the influence of values, beliefs and norms on social entrepreneurial intention of working adults in China. The cross-sectional design was employed, and an online survey, which involved 1,075 working adults, was conducted. All data were analyzed using partial least squares-structural equation modeling (PLS-SEM). The obtained results showed the significant and positive influence of self-enhancement, openness to change, and self-transcendence on the sense of meaning and purpose. Moreover, the sense of meaning and purpose exhibited significant and positive influence on problem awareness, and problem awareness was found to have positive effect on outcome efficacy. Besides that, the sense of meaning and purpose, problem awareness, outcome efficacy, and injunctive social norms were found to exhibit significant and positive on personal norms. Finally, personal norms and injunctive social norms exhibited statistically significant and positive influence on social entrepreneurial intention. The results of effect size confirmed the considerable influence of personal norms and injunctive social norms on social entrepreneurial intention. Therefore, policy development aimed at promoting socioeconomic and environmental sustainability through social entrepreneurship should comprehensively consider the influence of personal norms and injunctive social norms. Increasing the sense of meaning and purpose of the working population, prompting an increased problem consequence and outcome self-efficacy, as well as instilling personal norms and injunctive social norms through various social and environmental incentives are recommended.